Miradas y perspectivas de la educación matemática desde la formación, la inclusión y la tecnología - Solórzano Movilla, José (Corporación Universitaria Americana, 2020)
In this book, the result of research, a tour is made through several lines of work in mathematics education, such as teacher training, statistics education, didactics in virtual learning environments, inclusion and integration of ICT in mathematics education. Consequently, the works presented show how, from different points of view, research generates new reflections and experiences worthy of being reproduced in any educational scenario.